Optimizing the layer arrangement in a three-layer absorber based on magneto-electric nanocomposite for enhanced microwave absorption. Issue 21 (1st November 2022) - Luo, Jie; Mahariq, Ibrahim; You, Kok Yeow; Mehrez, Sadok; Fayed, Mohamed; Alamri, Sagr
Abstract: The widespread use of RF/microwave communication devices in daily life will lead to human exposure to radiation with potential adverse health effects. In this paper, a new synthetic absorber layer material is investigated. Pure polyindole (D), Bi0.5 Nd0.5 FeO3 (M), and a mixture of Polyindole/Bi0.5 Nd0.5 FeO3 (D/M) were synthesized and their macroscopic and microscopic properties were analyzed. The procedure for synthesizing the three samples was described in detail. The physico-chemical properties of the synthesized composites were characterized using an X-ray diffractometer, a Fourier-transform infrared spectrometer, a vibrating-sample magnetometer, and a field emission scanning electron microscope. Besides, the constitutive parameters of the three synthesized samples were measured using Keysight 85071E material measurement software and a vector network analyzer from 2 GHz to 18 GHz. Then, the return loss and shielding effectiveness of each sample are predicted based on the measured constitutive parameters and analytical models. The three synthesized samples were laminated into three layers of absorbing material backed by a metallic plate. The return loss of the laminated three-layer composites with different layer arrangements was calculated and predicted. From the microscopic analysis results, the mixture of D and M has the physico-chemical properties of pure sample D and sample M. However, from the macroscopic analysis results, the mixture of D and M has constitutive parameters more likely to be pure sample M. The three-layer samples with the first layer of sample D, the second layer of the sample M, and the third layer of the sample D/M (the layer terminating with a metallic plate) provide lower return loss, RL (certain thickness of samples can achieve RL < −20 dB) and higher absorption bandwidth compared to other study samples.